Trust and the infodemic: reframing information threats in the realm of public health - Harriet Dwyer; Luisa Enria; Nadine Beckmann; Julie Leask (Critical Public Health, 2025)
Amidst polarisation, public health threats and economic uncertainty, there is a concern around the impact of an overabundance of information: the infodemic. In this paper we argue that:information threats are a symptom of eroded trust, not the cause. Instead of viewing the overabundance of information as the primary problem, it should be understood as a reflection of wider trust processes;focusing on rebuilding trust offers a more effective approach than simply managing the infodemic. This includes promoting transparency and accountability from decision makers and fostering genuine community engagement when designing policy andvaccine confidence serves as an example of how trust, rather than information alone, drives public health decision making.We conclude that through understanding and rebuilding trust, rather than problematising information and individual consumption of information, we can strengthen community level public health responses.